2013
DOI: 10.5897/ajar2013.7243
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals from Ficus sycomorus L. leaves act as insecticides and acaricides

Abstract: 94) as main parts. The bioactive phytochemicals from F. sycomorus leaves were reported to be more toxic as the fumigant toxicity tests than the contact phase to the tested insects. The concentrations at 0.1, 0.01 and 0.001% were found to be repellent to adult females of Tetranychus utricae, followed by Aphis craccivora and Sitophilus oryzae, respectively. Here we demonstrate that bioactive phytochemicals from F. sycomorus leaves have a wide range of insecticidal and acaricidal and could become an alternative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
9
1
1
Order By: Relevance
“…In addition, 29 compounds were identified in the ethanolic extract of Ficus sycomorus leaves by GC-MS analysis Table (9 3,4,Neo Inositols,Psoralene,Phytol,acetate,5,Methyl Palmitate,Palmitic Acid,Methyl (11E,Methyl Linolenate,Phytol,Methyl isostearate,Linoleoyl chloride,8,11,14,Quercetin 7,3', Similar results are reported by Romeh (2013) who found that the chemical analysis of vaporous from F. sycomorus leaves allowed identification of 1, 2 benzenedicarboxilic acid, diisooctyl ester (45.06%), n-Hexadecanoic acid (7.67%), 1H-pyrazole,4-Nitro (5.13%), 3-Hexen-1-ol, benzoate, Z (4.57%), oleic acid (4.30%), hexanedioic acid, bis (2-ethyl hexyl) ester (4.15%), methyl oleate (2.41%), 3-buten-2-one, 4-(2, 6, 6-trimethyl-1cyclohexen-1-yl) (2.08%), 9-octadecenoic acid (Z)-2hydroxy-1-(hydroxymethyl) ethyl ester (1.79%), benzene methanol (1.59%), Cycloheptasiloxane,tetradecamethyl (1.38%), Z, Z-3, 13-octadecadien-1-ol (1.31%), 2pentadecanone (1.27%), 1-methylbicyclo [4.1.0] heptanes 1-methylnorcarane (1.06%), L-linalool (1.04%), cyclohexene (1.03%) and methyl jasmonate (0.94%) as main parts.…”
Section: Gc-mass Analysis Of Fruits and Leaves Of Ficus Sycomorussupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, 29 compounds were identified in the ethanolic extract of Ficus sycomorus leaves by GC-MS analysis Table (9 3,4,Neo Inositols,Psoralene,Phytol,acetate,5,Methyl Palmitate,Palmitic Acid,Methyl (11E,Methyl Linolenate,Phytol,Methyl isostearate,Linoleoyl chloride,8,11,14,Quercetin 7,3', Similar results are reported by Romeh (2013) who found that the chemical analysis of vaporous from F. sycomorus leaves allowed identification of 1, 2 benzenedicarboxilic acid, diisooctyl ester (45.06%), n-Hexadecanoic acid (7.67%), 1H-pyrazole,4-Nitro (5.13%), 3-Hexen-1-ol, benzoate, Z (4.57%), oleic acid (4.30%), hexanedioic acid, bis (2-ethyl hexyl) ester (4.15%), methyl oleate (2.41%), 3-buten-2-one, 4-(2, 6, 6-trimethyl-1cyclohexen-1-yl) (2.08%), 9-octadecenoic acid (Z)-2hydroxy-1-(hydroxymethyl) ethyl ester (1.79%), benzene methanol (1.59%), Cycloheptasiloxane,tetradecamethyl (1.38%), Z, Z-3, 13-octadecadien-1-ol (1.31%), 2pentadecanone (1.27%), 1-methylbicyclo [4.1.0] heptanes 1-methylnorcarane (1.06%), L-linalool (1.04%), cyclohexene (1.03%) and methyl jasmonate (0.94%) as main parts.…”
Section: Gc-mass Analysis Of Fruits and Leaves Of Ficus Sycomorussupporting
confidence: 81%
“…The flower is spherical, greenish, and unisexual. It contains latex, like all other figs (Romeh, 2013). The fruits of F. sycomorus are an important herbal medicine and food that is used to treat fungal infections, jaundice and dysentery (Hassan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The F. sycomorus extract has many medicinal properties, including antitumor [16], antimicrobial [6,17], and anti-inflammatory activities [18]. Moreover, this extract exhibited anticonvulsant [2] and sedative properties [6], antidiabetic activity [19], antidiarrheal activity [20], antioxidant activity [21], and insecticidal and acaricidal activities [22]. The extract also has hepatoprotective activity [12,23,24] and increases sperm cell production in rats [25].…”
Section: Introductionmentioning
confidence: 99%
“…The extracts of the fruits, leaves, stem and root barks usually administered in the form of infusions, decoctions, tinctures, syrups and lotions have been used in the treatment of many diseases and disorders such as tuberculosis, inflammations, dysentery, diarrhea, cough, chest and mental disorders, skin infections and helminthiasis 14&15 . Also, the plant was reported to have antimicrobial [16][17][18] , analgesic and anti-inflammatory 19 , antidiarrheal 20 , antioxidant 21 , hepatoprotective 15&22 , sedative and anticonvulsant 23 , antitumor 24 , antidiabetic 25 and muscle relaxant activities 26 in addition to insecticidal and acaricidal properties 27 .…”
Section: Introductionmentioning
confidence: 99%